Gambaran Proses Post-Traumatic Growth pada Atlet Paralimpiade dengan Kondisi Disabilitas yang Didapatkan Pasca Amputasi - Mellinia Putri, Nurfadli; Marita Lasutri Tama, Mulia (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
Paralympics is a sporting event for athletes with disabilities. Paralympic athletes' disability conditions can be obtained from birth or after birth such as chronic diseases, injuries due to war, riots, disasters, accidents, and so on. Accidents that are severe enough can cause serious medical conditions that can lead to amputation. Amputation can cause individuals to experience psychological trauma. In dealing with trauma, a person can experience a growth process until finally he can accept the situation that befell him, which is called post-traumatic growth. Post-traumatic growth is a positive change experienced by individuals after struggling in the face of trauma and is characterized by an improvement in self-quality compared to before experiencing trauma. This research was conducted in the city of Palembang on two paralympic athletes who were collected using the purposive sampling method. The data collection of this research was carried out by semi-structured interviews and active participation observations of the subjects. This study used a qualitative research design with a phenomenological approach. The findings of this study are that the process of forming post-traumatic growth begins with managing negative emotions and cognitive reflection until changes are achieved in oneself. Factors that can influence the formation of post-traumatic growth are hope, spirituality, social support, and the time since the traumatic event occurred.